Large-scale migration into Britain during the Middle to Late Bronze Age - Patterson, Nick; Isakov, Michael; Booth, Thomas; Büster, Lindsey; Fischer, Claire-Elise; Olalde, Iñigo; Ringbauer, Harald; Akbari, Ali; Cheronet, Olivia; Bleasdale, Madeleine; Adamski, Nicole; Altena, Eveline; et al. (Nature, 2022)
Present-day people from England and Wales have more ancestry derived from early European farmers (EEF) than did people of the Early Bronze Age1. To understand this, here we generated genome-wide data from 793 individuals, increasing data from the Middle to the Late Bronze Age and Iron Age in Britain by 12-fold, and western and central Europe by 3.5-fold. Between 1000 and 875 BC, EEF ancestry increased in southern Britain (England and Wales) but not northern Britain (Scotland) due to incorporation of migrants who arrived at this time and over previous centuries, and who were genetically most similar to ancient individuals from France. These migrants contributed about half the ancestry of people of England and Wales from the Iron Age, thereby creating a plausible vector for the spread of early Celtic languages into Britain. These patterns are part of a broader trend of EEF ancestry becoming more similar across central and western Europe in the Middle to the Late Bronze Age, coincident with archaeological evidence of intensified cultural exchange2-6. There was comparatively less gene flow from continental Europe during the Iron Age, and the independent genetic trajectory in Britain is also reflected in the rise of the allele conferring lactase persistence to approximately 50% by this time compared to approximately 7% in central Europe where it rose rapidly in frequency only a millennium later. This suggests that dairy products were used in qualitatively different ways in Britain and in central Europe over this period.
Keywords: Evropa; Archaeology; France; kojenec; genom lidský; Human Migration; United Kingdom; Infant; Spojené království; Humans; zemědělci; migrace lidstva; lidé; Farmers; Genome, Human; archeologie; Francie; Europe